2021
DOI: 10.1111/omi.12346
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of adhesion proteins to Aggregatibacter actinomycetemcomitans biofilm formation

Abstract: Aggregatibacter actinomycetemcomitans is a Gram‐negative bacterium associated with periodontal disease and multiple disseminated extra‐oral infections. Colonization of these distinct physiological niches is contingent on the expression of specific surface proteins during the initiation of developing biofilms. In this investigation, we studied fimbriae and three well‐characterized nonfimbrial surface proteins (EmaA, Aae, and ApiA/Omp100) for their contribution to biofilm formation. Mutations of these proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…The functionality of EmaA expressed in E. coli was determined by the ability of these cells to increase the mass of biofilm formed compared to the control cells, since the EmaA adhesin contributes to biofilm formation in A. actinomycetemcomitans independent of Waal ligase activity (26, 48). E. coli strain MG1655 formed very little biofilm, whereas transformation of this strain with the plasmid expressing emaA , under the regulation of the endogenous promoter, resulted in a greater than a 40-fold increase of the mass of the formed biofilm compared with the control strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionality of EmaA expressed in E. coli was determined by the ability of these cells to increase the mass of biofilm formed compared to the control cells, since the EmaA adhesin contributes to biofilm formation in A. actinomycetemcomitans independent of Waal ligase activity (26, 48). E. coli strain MG1655 formed very little biofilm, whereas transformation of this strain with the plasmid expressing emaA , under the regulation of the endogenous promoter, resulted in a greater than a 40-fold increase of the mass of the formed biofilm compared with the control strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A). Expression of emaA in another E. coli strain has been shown to enhance the biofilm potential of the cell (48). In both of the E. coli strains used in this study (MG1655 and a hemolytic strain synthesizing a complete O-PS) we also observed an increase in biofilm generated when EmaA was expressed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter regions of each of these adhesins contain predicted transcriptional regulator binding sites similar to those present in the emaA regulatory region (Figure 8). The promoters of aae and apiA have not been characterized, but our laboratory has used the intergenic regions as promoters in complementation studies (Danforth et al., 2021). The fimbrial ( flp ) promoter has been better characterized (Figurski et al., 2013; Kram et al., 2008), but extensive studies of the regulatory elements of the promoter have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical function of A. actinomycetemcomitans WaaL to ligate O‐PS to the core polysaccharide of LPS was confirmed by increased immunoreactivity of the transformed strain when compared with the E. coli waaL mutant, to a level similar to the parent strain (Figure 4a), even if this was not accompanied by an observable change in the O‐PS profile, must likely due to the lack of resolution of this gel system. Expression of emaA in another E. coli strain has been shown to enhance the biofilm potential of the cell (Danforth et al., 2021). In both of the E. coli strains used in this study (MG1655 and a hemolytic strain synthesizing a complete O‐PS), we also observed an increase in biofilm generated when EmaA was expressed (Figure 4b), which suggested that the adhesin was properly expressed and localized to the outer leaflet of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The functionality of EmaA expressed in E. coli was determined by the ability of these cells to increase the mass of biofilm formed compared to the control cells, because the EmaA adhesin contributes to biofilm formation in A. actinomycetemcomitans independent of Waal ligase activity (Danforth et al, 2019(Danforth et al, , 2021. E. coli strain MG1655 formed very little biofilm, whereas transformation of this strain with the plasmid expressing emaA, under the regulation of the endogenous promoter, resulted in a greater than a 40-fold increase of the mass of the formed biofilm compared with the control strain (Figure 4b).…”
Section: Functional Expression Of Waal and Emaa In E Colimentioning
confidence: 99%